2019
DOI: 10.3390/nu11092028
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Hospital Malnutrition in the African Continent

Abstract: This study aims to determine the prevalence of risk of malnutrition on admission and discharge in African hospitals, and to identify the association with selected indicators. In this multi-center prospective cohort study, adult patients from hospitals in South Africa, Kenya, and Ghana were screened on admission and discharge and contacted 3 months post-discharge. Relevant morbidity and mortality outcomes were assessed. At risk of malnutrition was indicated if NRS-2002 score ≥3. Adult patients (n = 2126; 43.11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
2
6
0
1
Order By: Relevance
“…Similar results have been published by some other authors, who reported a significant decrease in MAMC, fat-free mass, albumin level, weight and BMI during hospitalization. 7,9,10 In our study there was a decrease in the values of all NSAPs, except lymphocytes.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Similar results have been published by some other authors, who reported a significant decrease in MAMC, fat-free mass, albumin level, weight and BMI during hospitalization. 7,9,10 In our study there was a decrease in the values of all NSAPs, except lymphocytes.…”
Section: Discussionsupporting
confidence: 53%
“…[1][2][3] It significantly contributes to the many adverse outcomes, such as cardiovascular and infective complications, increased morbidity and mortality, prolonged hospitalization, increased hospitalization costs and increased re-admission rates after discharge from the hospital. [4][5][6][7][8] Although these consequences of poor nutritional status are well known, malnutrition is often undiagnosed on hospital admission. Furthermore, some patients have deterioration of the nutritional status and become malnourished during hospitalization, regardless of their initial nutritional status, but this change often remains unrecognized by the medical staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used the NRS-2002 to evaluate nutritional risk in hospitalized older PLWH. Although the NRS-2002 is a widely used tool in PLWH, some HIV-specific variables, such as viral load, are not included in this measurement tool [ 9 , 23 , 24 ]. In particular, HIV or AIDS, which is regarded as a chronic wasting disease, is also not included in first domain of the NRS-2002 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 11 In a small study of 25 patients, the average rate of malnutrition in hospitalized surgical patients in Malawi was 80%, which is double the world average. 12 , 13 …”
Section: Health and Nutrition Situation In Malawimentioning
confidence: 99%